Current strategies for ligand bioconjugation to poly(acrylamide) gels for 2D cell culture: Balancing chemo-selectivity, biofunctionality, and user-friendliness - Wolfel, Alexis; Jin, Minye; Paez, Julieta I. (Frontiers in Chemistry, 2022)
Hydrogel biomaterials in combination with living cells are applied in cell biology, tissue engineering and regenerative medicine. In particular, poly(acrylamide) (PAM) hydrogels are frequently used in cell biology laboratories as soft substrates for 2D cell culture. These biomaterials present advantages such as the straightforward synthesis, regulable mechanical properties within physiological range of native soft tissues, the possibility to be biofunctionalized with ligands to support the culture of living cells, and their optical transparency that makes them compatible with microscopy methods. Due to the chemical inertness and protein repellant properties of PAM hydrogels, these materials alone do not support the adhesion of cells. Therefore, biofunctionalization of PAM gels is necessary to confer them bioactivity and to promote cell-material interactions. Herein, the current chemical strategies for the bioconjugation of ligands to PAM gels are reviewed. Different aspects of the existing bioconjugation methods such as chemo-selectivity and site-specificity of attachment, preservation of ligand’s functionality after binding, user-friendliness and cost are presented and compared. This work aims at guiding users in the choice of a strategy to biofunctionalize PAM gels with desired biochemical properties.